Prevalence of Respiratory Diseases and Epidemiological Behavior of COVID-19 in Patients of the "Centro Histórico" Health Center, period March-May 2020 (International Seven Journal of Multidisciplinary, 2023)
The objective of this study was to determine the prevalence of respiratory diseases and the epidemiological behavior of COVID-19 in patients of “Centro Histórico” Health Center, March-May 2020 period. Observational, cross-sectional and descriptive study; in which the records of 1836 patients with respiratory symptoms were analyzed, using measures of central tendency and absolute and relative frequencies. The results revealed that the prevalent age range was 18 to 40 years with 707 (38.5%) cases; upper respiratory diseases were more frequent with 1617 (88.1%) cases. COVID-19, unidentified virus, was present in 91 (4.9%) cases, the older adult population being the most affected with 36 (39.5%) cases. There were 48 (2.6%) patients under home monitoring for suspected COVID-19, cough was the most frequent symptom (60.4%), and arterial hypertension (33.3%) was the most prevalent comorbidity in this group. More studies are required at the first level of care.